The Purposes of Tasybih Used in The Novel Sununuwati Kabul by Yasmina Khadra (Rhetoric Analysis) - Rahmi, Hafizatur; Permatasari, Dwi Nanda (Universitas Ahmad Dahlan, 2023)
Balaghah Anaylis has a fundamental goal namely, to convey the beauty of the grammar of language conveyed by the author in prose to convey the intended purpose to the readers especially in the novel Sununuwati Kabul by Yasmina Khadra. The author of the novel Sununuwati Kabul uses the tasybih language style to convey ideas and goals. In this study, the researcher used a qualitative type of research in which this study was more of a description or explanation of existing data for the research method, the researcher used the descriptive analysis method. This method is done by explaining or describing the data, followed by analyzing the data using a predetermined theory. As for the data collection technique، the researcher uses the library research method or library research to explain the data in this study. The results of this study are that there are 65 data on tasybih language styles in the novel Sununuwati Kabul by Yasmina Khadra، agrodu wa fawaidut tasybih by Yasmina Khadra، there are five types namely explaining the state of musyabbah explaining the size of the state of musyabbah determining the state of musyabbah decorating the musyabbah and vilifying the musyabbah.